Analisis Investasi Modal Dalam Pengembangan Usaha CV Ortidjoe Utama Group - Susilowatik, Anik; Yani, Ahmad; Naruli, Akhmad (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
One of the bakery businesses in Kediri, namely CV Ortidjoe Utama Group, has a new branch development with its own capital that has not been realized because it does not have a good financial analysis. Management with good capital investment analysis is expected to minimize failure. Financial analysis techniques that can be used include Payback Period, Accounting Rate of Return, Profitability Index, Internal Rate of Return and Net Present Value. The results of the study showed that the PP method for 1 year 1.7 months with a PP standard of ≤ 2 years is feasible to run. The ARR method is 87.6% with an ARR standard> 8.375% taken from the FR0076 bond coupon, so the business is feasible to run. The PI method is 1.752 with a PI standard> 1, so it is feasible to run. The IRR method is 47.12763634% with an IRR standard> 8.375% taken from the FR0076 bond coupon, so the business is feasible to run. The NPV method is Rp89,002,928.80 with an NPV standard> 0, so the business is feasible to run. The results of the calculations of the five methods stated that the development of the Ortidjoe Bakery business was feasible.